Experiences of and attitudes towards injecting drug use among marginalised African migrant and refugee youth in Melbourne, Australia - Horyniak, D.; Higgs, Peter; Cogger, S.; Dietze, P. (Taylor and Francis, 2014)
Little is known about injecting drug use (IDU) among people from culturally and linguistically diverse backgrounds in Australia. We interviewed 18 young people of African ethnicity (6 current/former injectors, 12 never injectors) about exposure and attitudes to IDU. Exposure to IDU was common, with IDU characterised as unnatural, risky and immoral. IDU was highly stigmatised and hidden from family and friends. There is a need for culturally appropriate programs to promote open dialogue about substance use, in order to reduce stigma and prevent African youth who may use illicit drugs from becoming further marginalised.